2005
DOI: 10.1088/0957-4484/16/12/066
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of biomolecule–copolymer hybrid nanovesicles as energy conversion systems

Abstract: This work demonstrates the integration of the energy-transducing proteins bacteriorhodopsin (BR) from Halobacterium halobium and cytochrome c oxidase (COX) from Rhodobacter sphaeroides into block copolymeric vesicles towards the demonstration of coupled protein functionality. An ABA triblock copolymer-based biomimetic membrane possessing UV-curable acrylate endgroups was synthesized to serve as a robust matrix for protein reconstitution. BR-functionalized polymers were shown to generate light-driven transmembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In fact, it was shown that a steric contraction of the hydrophilic components during polymerization was observed as well [21]. Without cross-linking, the 4 nm-thick polymer produced a low activity of bacteriorhodopsin due to the instability of the membrane as well as an inability to prevent transmembrane ion flux [22]. The jDpHj commonly peaked at 30-50 min around to a level around 0.1 (as shown, jDpHjZ 0.0953 at 50 min) and exhibited a large decrease of 57.71% in 2 h. These results indicate that although membrane leakage to ions in non-cross-linked polymer membranes was observed, the polymer membrane stability was far improved over that of the lipid membranes considering the experiments were conducted at room temperature.…”
Section: Rapid Reconstitution Of Protein In Varying Polymer Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it was shown that a steric contraction of the hydrophilic components during polymerization was observed as well [21]. Without cross-linking, the 4 nm-thick polymer produced a low activity of bacteriorhodopsin due to the instability of the membrane as well as an inability to prevent transmembrane ion flux [22]. The jDpHj commonly peaked at 30-50 min around to a level around 0.1 (as shown, jDpHjZ 0.0953 at 50 min) and exhibited a large decrease of 57.71% in 2 h. These results indicate that although membrane leakage to ions in non-cross-linked polymer membranes was observed, the polymer membrane stability was far improved over that of the lipid membranes considering the experiments were conducted at room temperature.…”
Section: Rapid Reconstitution Of Protein In Varying Polymer Constructsmentioning
confidence: 99%
“…As such, this would have possibly resulted in commonly observed 50/50 monomer orientations to decrease unidirectional pumping capabilities. In addition, polymer shielding effects could have also played a role in light scattering while not allowing the maximum amount of light to reach and activate the protein [21,22]. The shielding effects seemed to be far greater with bacteriorhodopsin monomers compared with polymers containing reconstituted purple membrane.…”
Section: Chemical Orientation Of Proton Pumpsmentioning
confidence: 99%
“…We have developed a technology that addresses the requisite strategies towards the fabrication of novel nanoprobe technologies that are capable of non-invasively stimulating or sensing cellular activity with attenuated inflammatory gene program responses. Versatile block copolymer materials that can be functionalized with anti-inflammatories such as dexamethasone, or various proteins, and tailored to possess varying stiffness properties have been developed as biocompatibility-enhancing modalities [6][7][8][9][10][11][12][13]. In addition, their amphiphilic nature enables their Langmuir-Blodgett (LB)-mediated transfer onto substrates for robust interfacing.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Significantly, bR has recently been shown to decrease pH locally. [12,13] This then provides the mechanism of actuation when combined with poly(acrylic acid), a pH-responsive polymer. [1] We chemically conjugated amine-terminated poly(acrylic acid) (PAA-a, depicted by the black monomer structure in Scheme 1) to the EC side of bR, thus orienting the trajectory of proton transport towards the polymer chain.…”
mentioning
confidence: 99%